'The Word of Yahweh is right': Psalm 33 as a Torah-psalm - Botha, Phil J.; Potgieter, J. Henk (Verbum et Ecclesia, 2010)
This article investigates some of the similarities between the Torah-psalms and Psalm 33. It is suggested that the ‘Torah-psalms’ should be re-contextualised and understood as part of a post-exilic endeavour to provide an interpretation of the emerging ‘canon’ of Hebrew scripture for the faithful of the late Persian period. Psalm 33 can also be counted amongst the literary products of this endeavour. The service it rendered to its audience was to establish a connection between Yahweh’s work of creation, his redemption of Israel and his divine rule over all the world through the power of his ‘word’.
free